Paradigma Keagamaan Dosen Pendidikan Agama Islam di Universitas Tirtayasa Banten - Huriyudin Huriyudin (Badan Litbang dan Diklat Kementerian Agama RI, 2021)
Abstract This study aims to explain the religious paradigm of lecturers in Islamic religious education at Tirtayasa University, Banten, using a qualitative approach. The research was conducted from April to June 2021. Data collection techniques used interviews, and content analysis. The informants involved were all lecturers of Islamic religious education. This study found that there were variations in religious paradigms, educational background and scientific interests, access to sources and reading materials, as well as religious styles adopted. The book used contains an acute problem related to the problem of religious moderation. The discussion on the themes of monotheism and Islamic theology has a significant difference with the general attitude of the people of Banten and its surroundings. An important implication of the results of this study is that several themes on history, Islamic social and political thought, as well as the science of monotheism and the science of kalam need to be reviewed, enriched by references, and further enrich the sources of religious thought. Â Abstrak Penelitian ini bertujuan untuk menjelaskan paradigma keagamaan dosen mata kuliah pendidikan agama Islam pada Universitas Tirtayasa Banten, dengan menggunakan pendekatan kualitatif. Penelitian dilakukan pada bulan April hingga Juni tahun 2021. Teknik pengumpulan data menggunakan wawancara, dan konten analisis. Informan yang terlibat adalah seluruh dosen pendidikan agama Islam. Penelitian ini menemukan adanya variasi paradigma keagamaan, latar belakang pendidikan dan minat keilmuan, akses terhadap sumber dan bahan bacaan, serta corak keagamaan yang dianut. Buku yang digunakan mengandung problem akut terkait dengan masalah moderasi beragama. Bahasan tentang tema-tema tauhid dan teologi Islam memiliki perbedaan yang signifikan dengan anutan umum masyarakat Banten dan sekitarnya. Implikasi penting dari hasil kajian ini, beberapa tema tentang sejarah, pemikiran sosial dan politik Islam, serta ilmu tauhid dan ilmu kalam perlu dilakukan peninjauan ulang, pengayaan referensi, dan lebih memperkaya nuktah-nuktah pemikiran keagamaan.